Demographic Determinants of Savings: Estimating and Interpreting the Aggregate Association in Asia - T. Paul Schultz (Yale University, Economic Growth Center, 2004)
Life cycle savings is proposed as one explanation for much of the increase in savings and economic growth in Asia. The association between the age composition of a nation's population and its savings rate, observed within 16 Asian countries from 1952 to 1992, is re-estimated here to be less than a quarter the size reported in a seminal study, which assumed lagged savings is exogenous. Specification tests as well as common sense imply, moreover, that lagged savings is likely to be endogenous, and when estimated accordingly there remains no significant dependence of savings on the age composition, measured in several ways. Research should consider lifetime savings as a substitute for children, and model the causes for the decline in fertility which changes the age compositions and could thereby account for savings and growth in Asia.
Keywords: D91; J11; O11; O53; 330; Life Cycle Savings; Aging; Asian Growth; Demographic Transition; Sparen; Lebenszyklus; Wirtschaftswachstum; Asien; Altersstruktur der Bevölkerung